2014
DOI: 10.1111/bjd.12781
|View full text |Cite
|
Sign up to set email alerts
|

Hyporeflective pagetoid cells: a new clue for amelanotic melanoma diagnosis by reflectance confocal microscopy

Abstract: The identification of HPCs in the epidermis is a new parameter that is frequently found in amelanotic melanoma. Possible confounders are represented by atypical keratinocytes that can be present in nonmelanocytic lesions. However, the whole architecture and the presence of additional diagnostic criteria should be considered in order to obtain a correct diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…On confocal microscopy there are few studies that reported characteristics of this type of melanoma [16,17,18,19,20]. Recently, hyporeflective pagetoid cells have been claimed as a new clue in the diagnosis of amelanotic melanoma [21]. In the same paper, the authors suggest that a solitary hypopigmented lesion, in the absence of any specific nonmelanocytic or melanocytic features, should always be excised due to the probability of melanoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…On confocal microscopy there are few studies that reported characteristics of this type of melanoma [16,17,18,19,20]. Recently, hyporeflective pagetoid cells have been claimed as a new clue in the diagnosis of amelanotic melanoma [21]. In the same paper, the authors suggest that a solitary hypopigmented lesion, in the absence of any specific nonmelanocytic or melanocytic features, should always be excised due to the probability of melanoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that RCM improves the ability to correctly identify both nevi and early melanomas in red-haired and fair skin–type patients, such as those with albinism. 3234 …”
Section: Role Of Reflectance Confocal Microscopy In Detecting Melanommentioning
confidence: 99%
“…In such lesions, melanocytes and pigmented keratinocytes appear very bright compared with background tissue, rendering a distinctive contrast to architectural and cellular details. Most recently, some publications reported RCM features observed in pink, hypopigmented, or amelanotic lesions; in those entities, the reflectance is provided by melanosomes and intracellular organelles of approximately 500 nm in diameter, especially in the background of a completely amelanotic tissue surrounding the tumor [6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%